Effects of chitosan molecular weight and deacetylation degree on the properties of collagen‐chitosan composite films for food packaging. Issue 41 (5th August 2022) - Zheng, Tingting; Tang, Pingping; Li, Guoying
Abstract: Composite films based on collagen and chitosan with different molecular weights (MWs) and deacetylation degree (DD) are prepared for food packaging. Fourier‐transform infrared analysis indicates that more hydrogen bonds have formed between collagen molecules and chitosan with larger MW or higher DD due to their more reactive groups for interactions. The light barrier capacity, mechanical, and thermal properties of the composite films enhanced with increasing the MW or DD of chitosan. However, composite film with the lowest MW of 50 kDa possesses the best antioxidative and antibacterial activities. Among all the films, composite films containing chitosan with low MW of 50 kDa and high DD of 95% exhibit better preservation effect in pork. The shelf life of pork wrapped with film containing chitosan of 50 kDa has been extended to 3 days with the lowest total volatile basic nitrogen level (12.13 mg/100 g), thiobarbituric acid reactive substance value (0.541 mg malondialdehyde/kg) and total viable count (5.64 log colony forming unit/g). These results indicate that MW and DD of chitosan are two important factors that should be considered when designing collagen‐chitosan composite films for food packaging. Abstract :